Satellite communications payload and system - Braun, T. M., 1949- (Wiley, 2012)
"This book is a unique combination of practical payload systems engineering and communications theory and applications. Payload systems engineering itself is a complex endeavor that people only learn on the job over many years' time, and this book hopes to ease their learning path. There are detailed books on how to design the various kinds of units, e.g., antennas, of a payload but seemingly no books focusing on unit performance at a level appropriate for systems engineering. Potential satellite owners, few of whom have worked in the satellite field, need help to understand how to get what they want from the manufacturer. The satellite bus, particular satellites, and particular and general satellite communications systems have been written about in several books, but the payload has received typically a few pages in all these books"--